2014
DOI: 10.1177/2047487314535682
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health-related quality of life predicts 5-year mortality and hospital readmissions in patients with ischaemic heart disease

Abstract: This study shows a significant and linear relationship between lower global and physical HRQL scores in patients with IHD and 5-year all-cause mortality and cardiac readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…Existing literature suggests that lower functional status increases the probability of readmission across different settings and conditions, including the Veterans Health Administration, 19 rehabilitation settings, [20][21][22] and in acute hospitals for heart conditions, [23][24][25][26][27] chronic obstructive pulmonary disease, 15,[28][29][30] burn injuries, 31 and all-cause readmissions. 19,[32][33][34] However, acute care studies have been based on small sample sizes ranging from 45 to 938 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature suggests that lower functional status increases the probability of readmission across different settings and conditions, including the Veterans Health Administration, 19 rehabilitation settings, [20][21][22] and in acute hospitals for heart conditions, [23][24][25][26][27] chronic obstructive pulmonary disease, 15,[28][29][30] burn injuries, 31 and all-cause readmissions. 19,[32][33][34] However, acute care studies have been based on small sample sizes ranging from 45 to 938 patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, several prior studies have demonstrated cardiovascular disease has a significant effect on patient-reported quality of life. 28,29 In conclusion, complications after cardiac operation continue to negatively influence patient quality of life 1 year after surgery. Use of the NIH-PROMIS showed prolonged ventilation, renal failure, stroke, and composite major morbidity have the largest impact on 1-year PROs.…”
Section: Commentmentioning
confidence: 99%
“…Two HRQoL questionnaires have recently been shown to allow for comparison among different diagnostic groups -the HeartQol and the MacNew [130][131][132]. The HeartQol, in particular, has demonstrated validity across 22 countries and several languages and has been shown to predict 5-year mortality and cardiac readmissions in patients with ischaemic heart disease [133]. Aside from evaluating the effectiveness of CR, this measure may also aid in identifying patients at higher risk for CVD events and thus inform treatment planning [134].…”
Section: Health-related Quality Of Lifementioning
confidence: 99%